Frictional properties and 3-D stress analysis of the southern Alpine Fault, New Zealand. (September 2018) - Boulton, Carolyn; Barth, Nicolas C.; Moore, Diane E.; Lockner, David A.; Townend, John; Faulkner, Daniel R.
Abstract: New Zealand's Alpine Fault (AF) ruptures quasi-periodically in large-magnitude earthquakes. Paleoseismological evidence suggests that about half of all recognized AF earthquakes terminated at the boundary between the Central and South Westland sections of the fault. There, fault geometry and the polarity of uplift change. The South Westland AF exhibits oblique-normal fault motion on a structure oriented 052°/82°SE that, for at least 35 km along strike, contains saponite-rich principal slip zone gouges. New hydrothermal friction experiments reveal that the saponite fault gouge is frictionally weak, exhibiting friction coefficients between μ = 0.12 and μ = 0.16 for a range of temperatures ( T = 25–210 °C) and effective normal stresses ( σ n ' = 31.2–93.6 MPa). The saponite gouge is rate-strengthening in all velocity steps performed at velocities between 0.01 and 3.0 μm/s, behavior conducive to aseismic creep. A three-dimensional stress analysis shows that the South Westland AF is favorably oriented with respect to the regional stress field for slip within the frictionally weak saponite fault gouge. Geometrically, the fault is severely misoriented for slip in any fault-forming materials with friction coefficients exceeding μ ∼0.5. The combination of weak gouges prone to aseismic creep, strong asperities, and low resolved shear stress may impede earthquake rupture propagation along the South Westland Alpine Fault. Highlights: Saponite gouge is frictionally weak across all conditions tested. The southern Alpine Fault is well-oriented for slip in weak gouge. Fault geometry and lithology impact rupture behavior.